PERAN MAHKAMAH KONSTITUSI DALAM MENJAGA STABILITAS KONSTITUSIONAL NEGARA - Muhammad Rafli; Rorry Pramudya; Yuli Fitriah (The Juris, 2026)
The existence of the Constitutional Court (MK) within the modern constitutional system is a fundamental pillar in upholding the principles of constitutionalism and limiting absolute governmental power. This normative study aims to analyze the strategic position of the Constitutional Court as the guardian of democracy and to identify the impact of challenges to judicial independence and ethical violations within the judiciary. Using statutory and conceptual approaches, data were collected through literature studies and analysis of relevant legal documents. The findings indicate that through the mechanism of judicial review, the Constitutional Court plays a crucial role in ensuring citizens' constitutional rights and in operating a system of checks and balances among state institutions. However, this institution also faces significant challenges related to the integrity and impartiality of its judges. Ethical violations by judges and legal misconduct by judicial actors have significantly reduced public legitimacy, threatened legal certainty, and triggered political distrust. Therefore, strengthening ethical sanctions through the Constitutional Court Honorary Council (MKMK) and enhancing internal oversight functions are essential prerequisites for maintaining the dignity of the highest judicial institution and preserving constitutional supremacy.